2017
DOI: 10.1097/ico.0000000000001479
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus and Personality—A Review

Abstract: We hypothesize that the stage of life at which keratoconus commonly presents plays a crucial role in personality and coping mechanism development that significantly affects behavioral patterns and the relationship with caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 14 publications
3
35
0
2
Order By: Relevance
“…7 Despite this, an important limitation of KORG is the fact that the mental sphere of patients is not taken into account for the measurement of their QoL. 4 The importance of the emotional component of patients with keratoconus was revealed by recent studies that have shown that patients with ectasia have different personality coping mechanisms, 9 and have a higher rate of depression. Given this aspect, it could be suggested that leaving aside the emotional sphere of patients could deprive the researcher and clinician of extremely important information to measure the true QoL of patients with keratoconus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Despite this, an important limitation of KORG is the fact that the mental sphere of patients is not taken into account for the measurement of their QoL. 4 The importance of the emotional component of patients with keratoconus was revealed by recent studies that have shown that patients with ectasia have different personality coping mechanisms, 9 and have a higher rate of depression. Given this aspect, it could be suggested that leaving aside the emotional sphere of patients could deprive the researcher and clinician of extremely important information to measure the true QoL of patients with keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been linked to particular different personality coping mechanisms. 9 Therefore, as has been highlighted before by Kandel et al, 4 it is of paramount importance that an instrument for the adequate measurement of the QoL in patients with keratoconus must necessarily include a component of the emotional sphere of the patients.…”
Section: Introductionmentioning
confidence: 97%
“…There may be personality traits that can moderate or mediate the perception of eye and vision problems. 4. Both groups of problems may at least partially share common risk factors, etiology, and pathophysiology.…”
Section: Concluding Considerationsmentioning
confidence: 99%
“…Some of them are so striking that special psychiatric states have been discussed and hypothesized. The best example is keratoconus personality, which is still under debate and has not yet been confirmed and a separate entity (4).…”
Section: Introductionmentioning
confidence: 99%
“… 2 KCN has a profound impact on the subjective quality of vision and life, especially in psychological aspects that might be overlooked by health-care providers. 3 Corneal collagen cross-linking (CXL) as a treatment that focuses on the underlying pathophysiology of the disease uses a combination of riboflavin (Vitamin B2) and ultraviolet-A (UV-A) light to strengthen the corneal tissue through photosensitization and chemical cross-linking. 4 5 Postoperative pain and complications resulting from epithelial debridement in the standard CXL procedure led to CXL without epithelial removal, known as transepithelial CXL.…”
Section: Introductionmentioning
confidence: 99%